Identifikasi dan Analisis Risiko Bahaya pada Proses Pembuatan Produk Gerabah Menggunakan HIRADC (Studi Kasus: UD. Putra Pendowo Kota Malang) - Sari, Faradilla Indah Oktavia; Renawati, Anggi; Fadholi, Azmi Burhan; Prawidiastri, Firnadila; Mountaz, Lotu; Pramesti, Nadila Ayu Setya (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
In pottery production centers, all activities involve risks that must be controlled to avoid losses. As for the pottery production houses which are included in the small industry, there is no maximum risk recognition and control for the workers and the company. Therefore, it is necessary to identify risks that may occur and determine controls so that risks can be minimized. The research was conducted at a pottery production house called UD Putra Pendowo with 10 workers. This research aims to identify risks at UD Putra Pendowo and formulate controls for the risks found. The method used in this research is descriptive observational with a cross sectional design which is carried out by making direct observations, while the hazard analysis method uses the HIRADC (Hazard Identification Risk Assessment and Determinant Control) method. From the research that has been carried out, there are 30 risks with Level 6 low risk, 16 medium risk and 8 high risk. It can be concluded that it is necessary to carry out controls to reduce risks in work at UD Putra Pendowo. Risk control that can be carried out is engineering by making tool covers that are prone to injuring hands, creating storage areas for certain equipment, and using tools such as trolleys; administration in the form of creating SOPs, safety signs, and education for workers; the provision and use of personal protective equipment.